Flamenco, flan, and fatalities - McHugh, Mary (McHugh, Mary. Happy Hoofers mystery., 2015)
"The high-kicking Happy Hoofers--Tina, Janice, Pat, Mary Louise, and Gini--have been booked to flaunt their fabulous flamenco footwork on a luxury train ride through northern Spain. But when a blowhard talk show host is found deader than four-day-old flan--with Gini as suspect numero uno--the feisty friends waste no time stepping into their sleuthing shoes to protect one of their own" --